The Indispensable Members: Reading 1 Corinthians 12:22–25 with Disability Theology for Inclusive Pedagogy in Christian Schools - Bobby Kurnia Putrawan; Christian Ade Maranatha (Shift Key : Jurnal Teologi dan Pelayanan, 2026)
This article examines 1 Corinthians 12:22-25 through the lens of disability theology to develop a theological foundation for inclusive Christian education in Indonesia. Employing qualitative library research and analogical hermeneutics, the study engages Pauline theology alongside the works of Nancy Eiesland, Deborah Creamer, Thomas Reynolds, and Brian Brock. Three theological principles are identified: (1) weakness does not negate membership in the body of Christ, (2) members perceived as weaker deserve greater honor, and (3) mutual interdependence is divine design, not human failure. Building on these principles, the article proposes four creative pedagogical models appropriate for resource-constrained Indonesian settings: Universal Design for Learning adapted for low-resource environments, low-cost locally available assistive technologies, collaborative peer-supported learning, and the creation of physically and socially inclusive learning environments without expensive infrastructure. The article also articulates the indispensable role of the church and Christian community as partners, trainers, policy advocates, and practical supporters of families.